PEMANFAATAN BIOCHAR LIMBAH SAGU UNTUK MENINGKATKAN KETERSEDIAAN N, P, K, STOK KARBON TANAH DAN HASIL TANAMAN JAGUNG DI ULTISOL - , Ir. Hadidjah Latuponu, MP, Dr. Ir. Djaâfar Shiddieq, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research aims to achieve type and dosage of SWB that can reduce leaching of N, P, K and increase growth and yield of corn. The research consisted of five experiments stages: (1) preparation and characterization of SWB and Ultisol, (2) the effect of type and dosage SWB to growth of corn, (3) the effect of ameliorant and incubation period to leaching of N, P, and K, (4) the effect of ameliorant and NPK fertilizer to nutrient uptake and fertilizer efficiency, (5) the influence of ameliorant and NPK fertilizer to yield of corn and soil carbon stocks. Results of the analysis showed that SWB has a lower N content than SWC, while the content of C, P, and K were higher. Proximate analysis showed SWB contain 45.22% solid carbon, 34.65% volatiles, 21.79% ash and 2.44% water. SWB (8.87 cc g-1) also have a higher pore volume than the SWC (4.45 cc g-1). The second experiment showed the most optimal dose of SWB for corn growth is 6 tonnes/ha. The application of SWB and SWC on Ultisols had higher buffering capacity than without ameliorant (the third Experiment). The high buffering capacity leads to lower leaching of N, P and K. Along incubation, some chemical properties of the soil column were given ameliorant after leaching showed increasing pH, carbon and CEC. Non amelioration soil has pH, CEC and organic C content was low, while the exchangeable Al was high. Increased nutrient uptake in plants better in Ultisol fertilized and given ameliorant, which further increases the efficiency of fertilization. Fertilizer efficiency in applied of SWC with 50% NPK fertilizers was 43,78% N